Taxonomy, taphonomy and chronology of the Pleistocene faunal assemblage at Ngalau Gupin cave, Sumatra. (30th November 2021) - Smith, Holly E.; Price, Gilbert J.; Duval, Mathieu; Westaway, Kira; Zaim, Jahdi; Rizal, Yan; Aswan,; Puspaningrum, Mika Rizki; Trihascaryo, Agus; Stewart, Mathew; Louys, Julien
Abstract: Ngalau Gupin is a broad karstic cave system in the Padang Highlands of western Sumatra, Indonesia. Abundant fossils, consisting of mostly isolated teeth from small-to large-sized animals, were recovered from breccias cemented on the cave walls and unconsolidated sediments on the cave floor. Two loci on the walls and floors of Ngalau Gupin, named NG-A and NG-B respectively, are studied. We determine that NG-B most likely formed as a result of the erosion and redeposition of material from NG-A. The collection reveals a rich, diverse Pleistocene faunal assemblage (Proboscidea, Primates, Rodentia, Artiodactyla, Perissodactyla, Carnivora) largely analogous to extant fauna in the modern rainforests of Sumatra. The hippopotamid Hexaprotodon represents the only globally extinct taxon in deposits from Sumatra and the first record of this animal from the island. This fossil assemblage is dated using combined U-series/ESR dating analyses of several teeth that yield a finite age of between 160 and 115 ka, depending on the modalities of the dose rate evaluation. Moreover, a direct U-series age estimate of 70 ka is obtained on the Hexaprotodon specimen, providing a minimum age constraint for the fossil that is compatible with the combined U-series/ESR results. These results suggest that the faunal assemblage at Ngalau Gupin correlates with late MIS 6 or early MIS 5. Ngalau Gupin likely reflects the formation of a fossil assemblage with two primary taphonomic pathways: a prime-aged dominated macrofauna component initially produced by carnivores but subsequently accumulated by porcupines and transported to the cave, and a microfauna component likely accumulated by small carnivores. Decalcification of the cemented deposit has further resulted in loss of fossil and other sedimentary material. This site adds important new chronologically constrained fossil mammal data for the Pleistocene record of Sumatra, an island relatively poorly investigated for Southeast Asia.